An Evaluation of Kant’s Transcendental Idealism Using the Inversion Theory of Truth - Peter Lugten (Journal of Philosophical Investigations, 2023)
This paper examines the work of Immanuel Kant in the light of a new theory on the nature of truth, knowledge and falsehood (the Inversion Theory of Truth). Kant’s idea that knowledge could be absolutely certain, and that its truth must correspond with reality, is discredited by a dissection of the Correspondence Theory of Truth. This examination of the nature of truth, as well as knowledge and falsehood, is conducted with reference to Sir Karl Popper’s writings on regulative ideas, the criterion of demarcation and the principle of falsifiability. It is argued that if truth is to be regarded as certain, it should be used to describe objects and events in the objective (noumenal) state, and that subjective knowledge must contain (and is improved by) falsehood. Perceptions and knowledge are obtained by the biological and evolutionary process of Active Subjectivism. Ideas we have knowledge of can be metaphysical or scientific, according to Popper’s Criterion of Demarcation. Kant’s “Copernican revolution” claim that our intellect imposes absolutely true laws on nature could not allow for the possibility that ideas might be constructed from fallible perceptions, and hence that all knowledge is uncertain. Instead, he developed a Critique of Practical Reason in which religion, though not provable through logical reasoning, could be proved by our innate moral sense, giving us a Categorical Imperative that could lead to perverse results. By rejecting the absolute certainty of a priori knowledge, and admitting a degree of essential falsehood, we arrive at a more reasonable grounding for moral behavior.